2016
DOI: 10.1128/aem.01048-16
|View full text |Cite
|
Sign up to set email alerts
|

The blp Locus of Streptococcus pneumoniae Plays a Limited Role in the Selection of Strains That Can Cocolonize the Human Nasopharynx

Abstract: Nasopharyngeal colonization is important for Streptococcus pneumoniae evolution, providing the opportunity for horizontal gene transfer when multiple strains co-occur. Although colonization with more than one strain of pneumococcus is common, the factors that influence the ability of strains to coexist are not known. A highly variable blp (bacteriocin-like peptide) locus has been identified in all sequenced strains of S. pneumoniae. This locus controls the regulation and secretion of bacteriocins, small peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…NZ_CP009913.1.). The bacteriocin cassette in the 24SMBc strain shows a genetic structure similar to that of the other blp operon already well characterized in S. pneumoniae and S. thermophilus (18,19,20); particularly, it is made up of three main modules: i) the ABC-transporters that recognize the N-termini of bacteriocins and transport these peptides out of the cell with the cleavage of the double-glycine motif, ii) the bacteriocin immunity module to protect the producer bacteria from the effects of their own bacteriocins, and iii) the peptide pheromone with a typical leader peptide containing a double-glycine motif. orf8 (180 bp) appears to be a structural gene, blpU-like, encoding 59 amino acids and a pore forming peptide belonging to bacteriocin class II with a double-glycine leader that could be important for its processing to its shorter mature peptide form.…”
Section: Genetic Organization Of the Blpu-like Bacteriocin Cassettementioning
confidence: 72%
See 2 more Smart Citations
“…NZ_CP009913.1.). The bacteriocin cassette in the 24SMBc strain shows a genetic structure similar to that of the other blp operon already well characterized in S. pneumoniae and S. thermophilus (18,19,20); particularly, it is made up of three main modules: i) the ABC-transporters that recognize the N-termini of bacteriocins and transport these peptides out of the cell with the cleavage of the double-glycine motif, ii) the bacteriocin immunity module to protect the producer bacteria from the effects of their own bacteriocins, and iii) the peptide pheromone with a typical leader peptide containing a double-glycine motif. orf8 (180 bp) appears to be a structural gene, blpU-like, encoding 59 amino acids and a pore forming peptide belonging to bacteriocin class II with a double-glycine leader that could be important for its processing to its shorter mature peptide form.…”
Section: Genetic Organization Of the Blpu-like Bacteriocin Cassettementioning
confidence: 72%
“…It is well known that bacteriocins play a fundamental role in the intra-and inter-species competition between the normal oral streptococcal species and pneumococci, contributing to maintain the complex equilibrium between a healthy state and the progression toward disease within the normal range (20,27) Streptococcus salivarius species is one of the pioneer strains, colonizing the oropharyngeal and gastrointestinal tracts in newborns, remaining predominant throughout the human life span, and capable of improving healthassociated oral and gut microbiota just by interfering with potential pathogens (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriocin production has been shown to inhibit competing strains in vitro and in murine models of colonisation (see, for example [17]). However, how this e↵ect translates to the epidemiological level is not entirely clear (see, for example [18]). In light of this uncertainty, we model two distinct ways in which the bacteriocin production could influence epidemiological dynamics in a homogeneously mixing host population.…”
Section: Model Structuresmentioning
confidence: 99%
“…A candidate for modulating densities of pneumococcal types had been the blp locus, which encodes a bacteriocin system that produces a potent bacteriocin, BlpC, but it has been recently demonstrated that BlpC plays a minor role in cocolonization (36,37). A secreted factor might not be involved in dominance of S19F strains by the S4 strain TIGR4, as demonstrated in experiments using Transwell systems, although our experimental design did not allow us to test for a factor(s) that could be only released when in close proximity.…”
Section: Figmentioning
confidence: 99%